Evoluç\~ao da formaç\~ao de engenheiros e profissionais técnico-científicos no Brasil entre 2000 e 2012 - Divonzir Arthur Gusso; Paulo A. Meyer M. Nascimento (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This paper analyses the evolution of tertiary education in Brazil from 2000 to 2012, with particular focus on Science, Technology, Engineering and Mathematics (STEM) fields. Administrative data are used to build indicators on the demand for courses, number of places, enrolments and graduates, and field concentration of the system output. The quality of the graduates is also briefly discussed, using as parameters the flows of new engineers graduating from top universities as well as the performance of Engineering graduating students on standardized tests administrated by the federal government. The evolution of such indicators is reported for: a) universities x other institutions offering tertiary education, classifying both types in publicly and privately-administrated; b) doctoral-granting institutions, as adapted by Steiner (2005, 2006) from the original Carnegie Classification of Institutions of Higher Education. Higher education institutions classified by Carnoy et al. (2013) as "elite institutions" are also considered as a separate group when quality matters are debated. The major objective of these efforts is to examine the context, dimension and quality of STEM human capital formation in Brazil from 2000 to 2012. Results suggest that the flow of new STEM graduates is expanding year after year in Brazil, but these numbers are still near to the ground in international standards and are concentrated on low-quality higher education institutions.
Keywords: I23; 330; higher education; STEM fields; engineers; Enade